High-power supercapacitors based on hierarchical porous nanometer-sized silicon carbide-derived carbon. (20th January 2016) - Yan, Pengtao; Xu, Jiang; Wu, Chao; Gu, Yu; Zhang, Xuesha; Zhang, Ruijun; Song, Yibo
Abstract: The nanoscale microporous carbide-derived carbon (nano-CDC) is synthesized by chlorination of silicon carbide nano-powder with a particle diameter around 60 nm and further pore-tuned by KOH activation with different KOH/nano-CDC ratios. Based on the higher specific surface area (SSA), a hierarchical micro- and meso-pore structure (especially for the greatly produced mesopores), and the shorter inherent ion transport distance within porous nano-carbons, the KOH-activated nano-CDC exhibits superior supercapacitive performances. Its specific capacitance is up to 141 F g −1, 156% increase compared with that of pristine nano-CDC (54 F g −1 ). Most interestingly, the cyclic voltammogram curve of the activated nano-CDC can keep a rectangular-like shape even at a scan rate of 5000 mV s −1, exhibiting significantly better power performance. This work confirms that constructing favorable pore structure in nanometer-sized porous carbons is an effective strategy for fabricating high-power supercapacitors.